Production and Optimization of Thermostable Alkaline Protease by Vibrio alginolyticus - S. Ramesh, A. Rebekkah Shanthakumari (Recent Research in Science and Technology, 2009)
Vibrio alginolyticus is a gram negative rod shaped bacterium which was enumerated in seawater from Chennai coast, Southeast coast of India. The isolates showed high thermostable alkaline protease activity which exhibited maximum at pH between 7.5 and 8.8 and maintains the stability at pH 8 at 36° C. The maximum activity of protease was found with 200 revolution per minute. The protease content was found to be 89% in V. alginolyticus. V. alginolyticus was resistance (95%) to Gentamycin and susceptible (100%) to Amikacin and Amoxyclav. The protease production did not show significant differences (P > 0.05) among concentrations of 15 µl, 20 µl and 25 µl in semi quantitative assay.